2018
DOI: 10.1200/jco.2018.36.5_suppl.188
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional anti-PD1 treatment in patients with metastatic melanoma: The pilot study.

Abstract: 188 Background: Systemic anti-PD1 treatment is major advantage for metastatic melanoma patients over the last five years. Nevertheless up to the moment there are no solid predictive factors discovered. On the other hand immune related adverse events develop quite frequent and sometimes could be dangerous. Methods: Patient with advanced cutaneous melanoma with known BRAF status and at least one superficial lesion (suitable for injection) are eligible. One of two commercially available anti-PD1 drugs (nivolumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Seven patients were treated with IT injections of either pembrolizumab or nivolumab in a phase I trial with dosing per a predetermined scale based on lesion size up to a maximum of 50 mg injected every 2 weeks. 31 Responses were seen in 4 patients. Of the 3 patients who had disease progression, 2 subsequently failed salvage systemic anti-PD-1 therapy.…”
Section: Cytokines and Other Tme Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven patients were treated with IT injections of either pembrolizumab or nivolumab in a phase I trial with dosing per a predetermined scale based on lesion size up to a maximum of 50 mg injected every 2 weeks. 31 Responses were seen in 4 patients. Of the 3 patients who had disease progression, 2 subsequently failed salvage systemic anti-PD-1 therapy.…”
Section: Cytokines and Other Tme Modulatorsmentioning
confidence: 99%
“…Finally, some studies have investigated the role of IT checkpoint inhibitors in patients with melanoma. Seven patients were treated with IT injections of either pembrolizumab or nivolumab in a phase I trial with dosing per a predetermined scale based on lesion size up to a maximum of 50 mg injected every 2 weeks 31 . Responses were seen in 4 patients.…”
Section: Cytokines and Other Tme Modulatorsmentioning
confidence: 99%
“…Interim analysis from a pilot study by Samoylenko et al recently demonstrated intralesional pembrolizumab or nivolumab resulted in an overall response in four out of the seven patients. 58 Additional studies are ongoing to study the safety and efficacy of intralesional CPI therapy in melanoma and other cutaneous malignancies, such as the use of intertumoral ipilimumab in combination with systemic nivolumab in patients with metastatic melanoma (NCT02857569) and the use of intratumoral nivolumab in patients with Kaposi’s sarcoma (NCT03316274).…”
Section: Intratumoral Strategiesmentioning
confidence: 99%